2008
DOI: 10.1074/jbc.m803413200
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Pro-sequence in the Secretory Pathway of Prothyrotropin-releasing Hormone

Abstract: The biogenesis of rat thyrotropin releasing hormone (TRH) involves the processing of its precursor (proTRH) into five biologically active TRH peptides and several non-TRH peptides where two of them had been attributed potential biological functions. This process implicates 1) proper folding of proTRH in the endoplasmic reticulum after its biosynthesis and exit to the Golgi apparatus and beyond, 2) initial processing of proTRH in the trans Golgi network and, 3) sorting of proTRH-derived peptides to the regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…In contrast, mutants lacking the hormone domain were present in the conditioned medium of transiently transfected cells. Notably, a similar finding was described previously for TRH constructs lacking the prodomain (75).…”
Section: Journal Of Biological Chemistrysupporting
confidence: 69%
“…In contrast, mutants lacking the hormone domain were present in the conditioned medium of transiently transfected cells. Notably, a similar finding was described previously for TRH constructs lacking the prodomain (75).…”
Section: Journal Of Biological Chemistrysupporting
confidence: 69%
“…At the TGN, proTRH products are sorted to and stored into specialized secretory granules (SGs) that undergo secretion only after appropriate stimuli. In these SGs the final processing steps take place, which involves endoproteolysis by specific prohormone convertases at pair of basic residues [82; 83; 84], removal of the basic residues by a carboxypeptidase [85; 86; 87], and amidation [5; 88]. If one of these regulated steps is compromised, the biosynthesis of the prohormone derived peptides and their secretion may be affected.…”
Section: Protrh Biosynthesis Processing and Trafficking To The Rementioning
confidence: 99%
“…1). By expressing several deletions and point mutations cDNA constructs within the preproTRH 31-52 sequence, and by monitoring the steady state production of proTRH in the ER, we identified a single tripeptide Pro-Gly-Leu ( 40 PGL 42 ) sequence, which is conserved in mammals and it turn out to be important for the stability of proTRH, in terms of resistance to protein degradation [84]. These studies revealed that PGL is primarily involved in the stability of proTRH in the early secretory pathway.…”
Section: Protrh Biosynthesis Processing and Trafficking To The Rementioning
confidence: 99%
See 1 more Smart Citation
“…A key intracellular function of LOX‐PP is most likely the maintenance of LOX in an inactive state within the secretory pathway [Kagan and Li, 2003]. Propeptides may also function as intramolecular chaperones to facilitate correct folding and the eventual targeting of these proteins to their destinations [Yasuda et al, 2005; Romero et al, 2008]. While the extracellular processing and activation of secretory pro‐LOX upon release of the propeptide moiety have been elucidated [Cronshaw et al, 1995; Panchenko et al, 1996; Uzel et al, 2001] the intracellular role of LOX‐PP within the secretory pathway has not been definitively described.…”
mentioning
confidence: 99%